Principal change leadership and e-learning effectiveness: The mediating role of teachers work commitment and attitudes toward change - Suryaman, Suryaman; Adha, Maulana Amirul; Suharyanto, Suharyanto; Ariyanti, Nova Syafira (Jurnal Cakrawala Pendidikan, 2024)
The purpose of this study was to determine the effect of the principals' change leadership on the effectiveness of online-based learning with teacher work commitment and teacher attitudes towards change as mediator variables, which were approached quantitatively. The population in this study were principals and teachers of public elementary schools, with a total sample of 378 respondents. The analytical technique used in this study is the Structural Equation Model (SEM), with the help of the Amos 24.0 program. The results of the study show that the principals' change leadership has a direct effect on the effectiveness of online-based learning, as well as an indirect effect through teacher work commitment and teacher attitudes towards change. This research contributes both theoretically and practically, where the change leadership demonstrated by the principal can ideally encourage teacher work commitment and teacher attitudes towards change, which in turn can promote the effectiveness of the implementation of online learning, as an effort to meet the learning needs of students.